The Interplay between Radioresistant Caco-2 Cells and the Immune System Increases Epithelial Layer Permeability and Alters Signaling Protein Spectrum - Morini, Jacopo; Babini, Gabriele; Barbieri, Sofia; Baiocco, Giorgio; Ottolenghi, Andrea (Frontiers in Immunology, 2017)
Colorectal cancer is one of the most frequent type of cancer, with a higher incidence in the developed countries. Colorectal cancer is usually managed with both surgery, chemotherapy and radiotherapy. Radiotherapy has the well-known advantage of targeting the tumor, minimizing normal tissue exposure. Nevertheless, during radiation treatment, exposure of healthy tissues is of great concern, in particular because of the effects on the intestinal barrier functions and on cells belonging to the immune system. The functional role of intestinal barrier in avoiding paracellular trafficking and controlling bacterial spread from gut it is well known and it is due to the presence of tight junction complexes. However, intestinal barrier is fundamental in participating to the interplay with immune system, especially considering the Gut Associated Lymphoid Tissue (GALT). Until few years ago, radiotherapy was considered to bear only a depressive action on the immune system. However, it is now recognized that the release of pro-inflammatory signals and phenotypic changes in tumoural cells due to ionizing radiation could trigger the immune system against the tumor. In this work we address how intestinal barrier functions are perturbed by X-ray doses in the range 0 - 10 Gy, focusing on the interplay between tumoural cells and the immune system. To this aim we adopted a co-culture model in which Caco-2 cells can be grown in presence/absence of Peripheral Blood Mononuclear Cells (PBMC). We focused our attention on changes in the proliferation, Trans-Epithelial Electrical Resistance (TEER), cytokine release and proteins of the junctional complexes. Our results indicate a high radioresistance of Caco-2 in the investigated dose range, and an increased permeability of the tumoural cell layer due to the presence of PBMC. This is found to be correlated with activation of PBMC, inhibiting the apoptotic pathway, with the enhancement of cytokine release and with variation of tight junction scaffold protein expression levels, assumed to be related to IFN-γ and TNF-α mediated signaling.